Media Informasi Wisata Kampung Adat Kuta Sebagai Salah Satu Aspek Dalam Perencanaan Pariwisata - Yunus Winoto; Gita Fitri Nuarini (Pusaka: Journal of Tourism, Hospitality, Travel and Business Event, 2022)
Dissemination of information is one of the efforts used for cultural tourism promotion activities. The purpose of this research is to determine the design process of information dissemination model for the promotion of cultural tourism attractions of the traditional village of Kuta, Karangpaninggal Village, Tambaksari District, Ciamis Regency, West Java. The approach used is action research based on the pattern of Kurt Lewin, which starts from planning, action, observation, and reflection. Data were obtained from the results of unstructured interviews and direct field observations. The results show that there is no information media used specifically to promote the tourist attractions of the traditional village of Kuta in the form of leaflets and booklets. Based on the stage of action research Kurt Lewin, in planning the researcher conducts planning based on communication planning or communication strategy that is starting from choosing a communicator, composing a message, determining the media, and determining the communicator.